The reader and the text - An applied study - Mahmoud, Ehab Majeed; Rashid, Abdul Salam Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
The researchers presented many studies on Al-Amadi as a critic. They have tackled specific aspects in his methodology and his critical attitude. However, the examination of the samples and the focus on the details of the critical approach did not provide research and applied studies that examine the text structures that may have many readings and vary in significance. The sample that we are studying in this paper has undergone several forms of deliberate change to hide the features of poetic identity produced by a poet who has a depth of vision. This vision qualifies him to lead the process of modernization in poetic performance in an era dominated by the influence of heritage extensively to stop the possibilities of overtaking and development in performance.